Effectiveness of Business Partnerships in Oil Palm Nucleus Estate and Smallholder Scheme in West and Central Kalimantan Provinces, Indonesia - Mokhtar, Muhammad Saleh (2005)
Nucleus Estate and Smallholders (NES) Scheme is a scheme of business partnership between estate company as " nucleus" and smallholders as "plasma". The objectives of this study were: (i) to examine the effectiveness of the business partnership from the smallholders' and estate companies' point of view, (ii) to identify the social and economic factors affecting effectiveness of the business partnership, (iii) to identify strategic factors of the business partnership from estate companies' point of view, (iv) to measure the perception of stakeholders towards the new estate cropsloil palm development models, and (v) to identify strategic factors for the implementation of the new estate crop models. This study comprises three sub studies. The first was a study on the effectiveness of business partnership in oil palm NES scheme from smallholders' point of view, based on 150 smallholder respondents chosen on a purposive multi stage stratified random 111 sampling. The second was a study on the effectiveness of business partnership in oil palm NES scheme from estate companies' point of view, based on 50 respondents, selected using purposive sampling. The third was a study on the perception of stakeholders on the new estate crops development models based on Ministry of Agriculture Decree No. 35712002, with 52 total respondents, chosen using purposive sampling. The study found that, in general, effectiveness of the business partnership in oil palm NES scheme in the study area was adequate, with an achievement rating scale of 692 or 69.2% of the maximum rating scale of 1,000. Effectiveness of the business partnership from both smallholders' and estate companies' point of views was adequate, with an achievement rating scale of 663 or 66.3% and 735 or 73.5% of the maximum rating scale, respectively. Results of the multiple regression analysis showed that seven of the 13 independent variables affecting effectiveness were found to be significant. They were: (1) commitment of estate companies (CCOM), (2) role of the estate companies (CORS) (3) role of smallholders' organizations (OFRS), (4) farm capital of smallholders (CAPL), (5) price of fertilizers used by smallholders (PFER), (6) distance of smallholders' home to oil palm plot (DIST), (7) types of ownership of the NES (OWNS). Results of path analysis showed that six of the seven variables i.e. DIST, OWNS, CCOM, CORS, OFRS, and PFER had both direct and indirect effects on effectiveness (EFES). CAPL, however, had only direct effect on EFES. CAPL, however, had the highest total positive effect on EFES, followed by OFRS, CCOM, OWNS, CORS, and PFER. While, DIST had a relatively high negative total effect on EFES. The economic factors that had a significant total effect on the effectiveness (EFES) were CAPL and PFER, and DIST; and the social factors that had a significant total effect on EFES were CCOM, CORS, OFRS, and OWNS. The other variables namely, estate company's cooperative behavior (COBS), smallholders' income from other sources (NFFI), satisfaction of smallholders (FSAT), smallholders' family labor participation (LABS), credit availability (CRED), and the government supports (GOVS) had insignificant total effect on EFES. Based on results of the SWOT analysis, it can be inferred that most of the internal strength and weaknesses factors affecting effectiveness of the business partnerships in oil palm NES Scheme were related to organization, followed by human resource, . . .marketing, and operation. On the other hand, most of the external opportunity and threat factors were related to economics, policy and ecology. Five strategies were recommended for improving the effectiveness of the business partnership in a descending order of priority. They are: (i) all parties involved, estate companies, government, and smallholders, should be very committed in carrying out their responsibilities and safeguarding their rights as stated in the contract agreement and the relevant government regulations, (ii) the government and estate companies should provide empowerment programs for smallholders, farmers' organizations, and officials at various levels, (iii) estate companies and smallholders should constantly improve cooperation and place each other as valued partners, (iv) estate companies and government should ensure constant supply of production inputslfertilizers to smallholders, and (v) top management of NES scheme should assist in strengthening capability of site management and their supporting staffs. - - - v Perception of the stakeholders towards the new oil palm development models was good, even though to implement them, investors and farmers' cooperatives would face many problems due to internal weaknesses and external threats. The internal strengths and weaknesses affecting implementation of the new oil palm development models were mostly related to human resource, organizations/institutions, and finance. On the other hand, the external opportunity and threat factors were mostly related to policy, economics and social and culture. Five strategies were recommended for accelerating the implementation of the new oil palm development models. In a descending order of priority, namely: (i) providing strong and clear regulations and guidelines; (ii) campaigning more to promote and familiarize the new models to investors, smallholders, and other stakeholders, (iii) providing empowerment programs for smallholders, and smallholders' organizations, (iv) reengineering mechanism to reduce unnecessary government bureaucracy in getting land use right (HGU); and (v) increasing assistance by the government to financial and risk institutions in providing services to smallholders.